Find solutions to your problems with the expert advice available on IDNLearn.com. Get the information you need from our community of experts who provide accurate and thorough answers to all your questions.
Sagot :
To find the vertex of the quadratic function [tex]\( y = x^2 - 6x + 1 \)[/tex], we can use the vertex formula for a parabola. The vertex of a parabola described by the quadratic equation [tex]\( y = ax^2 + bx + c \)[/tex] can be found using the following steps:
1. Identify the coefficients: From the given quadratic equation [tex]\( y = x^2 - 6x + 1 \)[/tex], we have:
- [tex]\( a = 1 \)[/tex] (coefficient of [tex]\( x^2 \)[/tex])
- [tex]\( b = -6 \)[/tex] (coefficient of [tex]\( x \)[/tex])
- [tex]\( c = 1 \)[/tex] (constant term)
2. Calculate the x-coordinate of the vertex: The x-coordinate of the vertex can be found using the formula:
[tex]\[ x = -\frac{b}{2a} \][/tex]
Substituting the values of [tex]\( a \)[/tex] and [tex]\( b \)[/tex] into the formula, we get:
[tex]\[ x = -\frac{-6}{2 \cdot 1} = \frac{6}{2} = 3 \][/tex]
3. Calculate the y-coordinate of the vertex: To find the y-coordinate, we substitute the x-coordinate back into the original quadratic equation [tex]\( y = x^2 - 6x + 1 \)[/tex]:
[tex]\[ y = (3)^2 - 6(3) + 1 = 9 - 18 + 1 = -8 \][/tex]
Therefore, the vertex of the quadratic function [tex]\( y = x^2 - 6x + 1 \)[/tex] is at the point [tex]\( (3, -8) \)[/tex].
The correct answer is:
D. [tex]\( (3, -8) \)[/tex]
1. Identify the coefficients: From the given quadratic equation [tex]\( y = x^2 - 6x + 1 \)[/tex], we have:
- [tex]\( a = 1 \)[/tex] (coefficient of [tex]\( x^2 \)[/tex])
- [tex]\( b = -6 \)[/tex] (coefficient of [tex]\( x \)[/tex])
- [tex]\( c = 1 \)[/tex] (constant term)
2. Calculate the x-coordinate of the vertex: The x-coordinate of the vertex can be found using the formula:
[tex]\[ x = -\frac{b}{2a} \][/tex]
Substituting the values of [tex]\( a \)[/tex] and [tex]\( b \)[/tex] into the formula, we get:
[tex]\[ x = -\frac{-6}{2 \cdot 1} = \frac{6}{2} = 3 \][/tex]
3. Calculate the y-coordinate of the vertex: To find the y-coordinate, we substitute the x-coordinate back into the original quadratic equation [tex]\( y = x^2 - 6x + 1 \)[/tex]:
[tex]\[ y = (3)^2 - 6(3) + 1 = 9 - 18 + 1 = -8 \][/tex]
Therefore, the vertex of the quadratic function [tex]\( y = x^2 - 6x + 1 \)[/tex] is at the point [tex]\( (3, -8) \)[/tex].
The correct answer is:
D. [tex]\( (3, -8) \)[/tex]
We appreciate your presence here. Keep sharing knowledge and helping others find the answers they need. This community is the perfect place to learn together. IDNLearn.com has the answers you need. Thank you for visiting, and we look forward to helping you again soon.